Profit Over Paradise: Exposing the Unsustainable Trajectory of Foreign Property in Canggu's Tourism Development - Dananjaya, Ahmad Ghazy (Journal of Indonesian Tourism and Development Studies, 2025)
This study examines the ethical implications of foreign property dominance in Canggu, Bali, following the post-pandemic surge in digital nomads. Using a mixed-method approach involving 400 respondents, the research analyzes the impact of this demographic shift on social inequality and environmental integrity. The results demonstrate a strong correlation between foreign property expansion and widening social gaps. Findings reveal that local residents perceive significantly higher environmental degradation compared to the expatriate population. Specifically, the "New Moscow" phenomenon has triggered the economic displacement of indigenous communities due to soaring rental prices and the destruction of the traditional Subak irrigation ecosystem. The study concludes that the current trajectory prioritizes profit over cultural preservation, resulting in a neo-colonial spatial structure that overlooks local wisdom. To safeguard Bali’s future, the research recommends an immediate moratorium on commercial permits in green zones, agricultural tax incentives, and stricter regulation of foreign ownership schemes to ensure sustainable and equitable tourism planning.